Women's Leadership in Education: Driving Local and Global Cultural Revolution - Naila Shopia Al Husna; Nancy; Burhan Uddin (Letiges, 2025)
This study aims to analyse women's leadership in education as a form of cultural revolution both locally and globally. The formulation of the problem in this study is compiled using the PCC formula (Population, Concept, Context), where P (Population) refers to women leaders in education; C (Concept) is women's leadership as the main variable; and C (Context) is the social and educational conditions in the local environment (Islamic boarding schools in Indonesia) and globally (world educational activism). The approach used is the Systematic Literature Review (SLR), with a systematic search strategy through academic databases such as Scopus, Google Scholar, and Web of Science. Search results are reported using PRISMA diagrams. Nyai Hj. Masriyah Amva, the head of the Kebon Jambu Islamic Boarding School in Cirebon, West Java, as a concrete example of a local figure who promotes gender equality in the Islamic education system. At the global level, the figure studied is Malala Yousafzai, an activist from Pakistan and founder of the Malala Fund, who actively fights for women's education rights through policy advocacy and cooperation with international institutions. The results of the study show that women's leadership is able to increase inclusivity, fight for gender justice, and accelerate social transformation. Local leadership like Bu Nyai stands out in adapting cultural and religious values, while global leadership like Malala focuses on policy-based structural change. Integration between local and global approaches is believed to be a sustainable strategy to create a more equal and transformative education system.